Implementation of an Automatic Capacitor Bank Control System Using PLC for Power Factor Optimization - Supriadi Marpaung; Moranain Mungkin (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
The efficiency and stability of electrical power systems are greatly influenced by the power factor. A low power factor can lead to increased losses and higher electricity bills, especially in industrial environments. This study presents the implementation of an automatic capacitor bank control system using a Programmable Logic Controller(PLC) to optimize the power factor in an electrical installation. The system is designed to monitor reactive and active power in realtime, and automatically switch capacitor banks on or off based on the load condition. By utilizing PLC technology, the system ensures precision, reliability, and ease of modification according to operational requirements. Testing results demonstrate a significant improvement in power factor after the system is applied, as well as reduced reactive power consumption. This research contributes to the development of smart, automated solutions for energy efficiency in industrial power management systems.